Case Report: Life-Threatening Macrophage Activation Syndrome With Fulminant Myocarditis Successfully Rescued by High Dose Intravenous Anakinra - Meneghel, Alessandra; Martini, Giorgia; Amigoni, Angela; Pettenazzo, Andrea; Padalino, Massimo; Zulian, Francesco (Frontiers in Pediatrics, 2021)
Macrophage activation syndrome (MAS) is a rare, potentially life-threatening, condition triggered by infections or flares in rheumatologic and neoplastic diseases. The mainstay of treatment includes high dose corticosteroids, intravenous immunoglobulins and immunosuppressive drugs although, more recently, a more targeted approach, based on the use of selective cytokines inhibitors, has been reported. We present the case of a two-years-old boy with one-month history of high degree fever associated with limping gait, cervical lymphadenopathy and skin rash. Laboratory tests showed elevation of inflammatory markers and ferritin. By exclusion criteria, systemic onset Juvenile Idiopathic Arthritis (sJIA) was diagnosed and steroid therapy started. A couple of weeks later, fever relapsed and laboratory tests were consistent with MAS. He was promptly treated with high doses intravenous methylprednisolone pulses and oral cyclosporin A. One day later, he developed an acute myocarditis and a systemic capillary leak syndrome needing intensive care. Intravenous Immunoglobulin and subcutaneous IL1-antagonists Anakinra were added. On day 4, after an episode of cardiac arrest, venous-arterial extracorporeal membrane oxygenation (VA-ECMO) was started. Considering the severe refractory clinical picture, we tried high dose intravenous Anakinra (HDIV-ANA). This treatment brought immediate benefit: serial echocardiography showed progressive resolution of myocarditis, VA-ECMO was gradually decreased and definitely weaned off in six days and MAS laboratory markers improved. Our case underscores the importance of an early aggressive treatment in refractory life-threatening sJIA-related MAS and adds evidence on safety and efficacy of HDIV-ANA particularly in acute myocarditis needing VA-ECMO support.